Micro- and macro-changes in early-stage type 2 diabetes mellitus without cognitive impairment: a diffusion tensor imaging (DTI) and surface-based morphometry (SBM) study - Tang, Xiangyong; Chen, Yanzi; Tan, Hui; Fang, Jinzhi; Yu, Dafei; Chen, Cuimei; Li, Xiao; Hu, Ziqi; Ding, Ling; Zhang, Yuzhong (Frontiers in Neurology, 2023)
Brain structure and function changes have been considered as the major brain damages of type 2 diabetes mellitus (T2DM), which might have closely relationship with cognitive impairment. Many previous studies demonstrated brain white and gray matter damaged in T2DM using brain structural and functional magnetic resonance imaging (MRI) methods, neglecting patients of T2DM without cognitive dysfunction also had brain changes. In this study, subjects of early stage T2DM with no cognitive dysfunction were absorbed to detect brain damages using tract-based spatial statistics analysis (TBSS) method to demonstrate WM micro changes and surface-based morphometry (SBM) method to assess cerebral cortex changes. The whole-brain TBSS analysis revealed that there were no statistically changes in fractional anisotropy (FA) and mean diffusivity (MD), but the FA declined in some area of cerebral (p < 0.1). SBM results presented there were no changes of cortical thickness (CT), cortical volume (CV), surface area (SA) and cortical sulcal curve (CSC) between these two groups, but pial local gyration index (LGI) declined in precuneus (-log10 p = -3.327). In conclusion, early stage T2DM patients without cognitive impairment had brain micro and macro structure damages, suggesting the potential use as an imaging marker for detecting brain changes in early stage T2DM, which could not be observed and assessed clinically.